Chemical studies of 3-pyrrolin-2-one for the synthesis of y-lactam y-lactone / Aimi Suhaily Saaidin - Saaidin, Aimi Suhaily (2015)
Unsaturated pyrrolidinone has been extensively studied due to its unique structure and its presence in various biologically active natural compounds. In this study, 3- pyrrolin-2 -one, 162 has been constructed via five steps which included condensation of glycine methyl ester and methyl malonyl chloride, Dieckmann cyclization, decarbomethoxylation, reduction and elimination with an overall yield of 33%. The synthesized compound 162 was then used as the intermediate for a few chemical transformations such as Michael addition and epoxidation reaction. Synthesis of fused bicyclic 3,4-y-lactone-y-lactam towards mescaline isocitrimide was also attempted. The synthetic approach was divided into two different routes. The first route began by insertion of dimethyl malonate onto the synthesized intermediate of 3 pyrrolin-2 -one via Michael addition reaction, followed by methylation of the P-diester and bromination at C3 position. However, the bromination reaction failed to give us the desired product which then diverted us to the second route. In this route, the y-lactoney- lactam ring system was successfully synthesized by coupling readily available benzylated glycine methyl ester and methyl malonyl chloride followed by Dieckmann cyclization, alkylation at C3 position and Krapcho decarboxylation. The fused bicyclic ring was afforded through stereoselective reduction which accompanied concomitant lactonization with an overall yield of 0.8%. In brief, we have developed an operationally simple procedure towards the synthesis of 3-pyrrolin-2-one and fused bicyclic 3,4-y-lactone-y-lactam ring skeleton. The results extracted from this study thus far may be used to develop new scientific knowledge and remarkable findings.